THE INFLUENCE OF EXTRUSION DIE ANGLE DURING THE HOT EXTRUSION PROCESS OF AL ALLOYS - Rezaei Ashtiani, Hamidreza (Journal of Advanced Manufacturing Technology (JAMT), 2016)
One of the most important parameters for the hot extrusion process effecting the deformation force, material flow, microstructural and mechanical properties of the extruded material is the Extrusion Die Angle (EDA). In this investigation, the effects of EDA on load, material flow and microstructure of hot extruded commercially pure aluminum has been studied. The Finite element simulation were carried out using Deform 3D. Finite element modeling shows that the values of the equivalent plastic strain and its distribution, flow material and deformation forces depend extremely on deformation temperature, reduction and EDA. To estimate the reliability of the numerical analysis, the FE model was validated using experimental results. The results showed that the lowest extrusion force occurs in an optimum die angle for each reduction. Optimum EDA obtained 16, 18 and 23 degrees at reductions of 50%, 60% and 70%, respectively. Also, material flow, inhomogeneity of microstructure and the equivalent plastic strain increases with increasing of EDA.